The Influence of Celebrity Endorser's Attractiveness, Trustworthiness, and Expertise towards Consumer Purchase Intention with Brand Image as a Mediating Variable: The Case of Samsung and BLACKPINK - Thalia Sugita; Nova Hendryani (iBuss Management, 2022)
The global competitiveness of the smartphone industry increases as the world shifts  nto a more digital and innovative-led economy. With the industr's growth, smartphone companies rely on promotion to strengthen their brand image and increase consumers' purchase intention. One of the promotional activities used by smartphone companies is celebrity endorsement. Samsung has also used celebrity endorsement in their promotional activities, and BLACKPINK is their celebrity endorser. Several marketing studies have shown that celebrity endorsement, especially in attractiveness, trustworthiness, and expertise showed a positive influence on brand image and purchase intentions. This research aims to find if there are similar results in Samsung with BLACKPINK as their celebrity endorser. The data will be taken from a minimum of 106 respondents whose ages are above 17. The process will be using simple random sampling and will be analyzed through PLS-SEM software. Findings show that there is a significant influence of attractiveness towards the brand image also brand image towards purchase intention. Moreover, brand image has a full mediation in the relationship between attractiveness and purchase intention. For the rest of the hypotheses, it shows a non-significant relationship. From the results, there are several limitations and suggestions that are described in the paper.Keywords: Celebrity endorsement, Attractiveness, Trustworthiness, EZxpertise, Samsung, Blackpink, Brand image, Purchase intention